New Dimensions of Musicology of the 21st Century: the Experience in Modelling the Interpretative Theory of Musical Communication - Nikolayevska, Yuliya (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The relevance of the topic is associated with the formulation of the basic principles of the theory of musical interpretation in its interpretative dimension. Novelty. The novelty of the research lies in the understanding of musical communication as an interpretative phenomenon. The purpose of the research is to propose a model of the interpretative theory of musical communication for the development of the existing concepts. Methodology. Based on the research in modern humanities (M. Bakhtin, J. Habermas, H. Gumbrecht, S. Zizek, M. McLuhan, E. Levinas, J. Austin, D. Sperber, U. Eco), the theory of musical communication (E. Turner, A. Yakupov, V. Medushevsky, B. Syuta) and the theory of musical interpretation (Jean-Jacques Nathiez, T. Adorno, J. Brele, H. Danuzer, E. Gurenko, N. Korikhalova, V. Medushevsky, V. Moskalenko, L. Shapovalova, A. Samoilenko) a new look at the artistic processes of the 20th and early 21st centuries has been proposed. The main is the modeling method. Results and conclusions. For the development of the classical and relevant theories of communication (the main difference of the first is the recognition as the central element of the system the composition as a code, the essence of the second — the existence as the central element of a “musical-communicative event” and attention to the intentions of the communicants, the context of events, which determines their adequate understanding), the model of the interpretative theory of musical communication, in which both approaches are combined, has been introduced. We have introduced into the conceptual apparatus of musical science the type of Homo Interpretatus, which is the creator of a new modern musical reality and can be designated as a summary image of a person who, in the process of musical activity, manifests the dominance of interpreting thinking (in the unity and variety of the functions “composer — performer — listener — researcher”). The concept of “communication strategy” has been proposed, which is understood as the conscious action of the communicant (the intention directed at the Other in the process of creative communication). The typology of communication strategies has been presented: taking into account the type of creative activity (composing, performing, researching, listening) and based on their different forms of working with the material / text, as well as the focus on perception (in particular, idioethnic, modelling, actualizing, integrating, the strategy of style divergence / convergence, active, passive, total randomness, etc.). Significance. The significance of the results lies in the systematic presentation of the positions of the interpretive theory of musical communication, which opens up prospects for further research on the interpretive processes of the 21st century.